Analisis Strategi Pengawasan Dalam Pemberian Pembiayaan Murabahah Guna Meminimalisir Resiko Pembiayaan Bermasalah Bagi Bank PT BPRS Alwashliyah Medan - Fattonah, Rindang Dwi; Marliyah, Marliyah; Syarvina, Wahyu (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2025)
Supervision activities are crucial for banks to prevent potential problems that may arise due to various factors during financing. This study aims to analyze the supervision strategies employed b.y PT BPRS al-Washliyah Medan, specifically on Murabaha contracts. A qualitative descriptive meth.od was used, emplo.ying da.ta colle.ction techn.iques through observ.ation, interv.iews, and documentation. Additionally, SWOT analysis was utilized as an instrument to evaluate the supervision strategies. The results show that PT BPRS al-Washliyah can implement proactive strategies by leveraging existing strengths and opportunities. Understanding this strategy will enable the bank to take more effective measures to enhance their supervision quality. This is expected to measure the role and ability of PT BPRS al-Washliyah in financing monitoring, as it has a positive impact on the bank